Cooperative Reinforcement of Ionic Liquid and Reactive Solvent on Enzymatic Synthesis of Caffeic Acid Phenethyl Ester as an In Vitro Inhibitor of Plant Pathogenic Bacteria - Xu, Yan (Molecules, 2017)
It is widely believed that lipases in ionic liquids (ILs) possess higher enzyme activity, stability and selectivity; however, reaction equilibrium is always limited by product inhibition, and the product is difficult to separate from non-volatile ILs using distillation. To solve this problem, using trialkylphosphine oxide (TOPO) as a complexing agent, a novel biphase of reactive solvent and IL was firstly reported for caffeic acid phenethyl ester (CAPE) production from methyl caffeate (MC) and 2-phenylethanol (PE) catalyzed by lipase via transesterification. The effects of the reaction parameters and their action mechanism were investigated, and the inhibition of CAPE against bacterial wilt pathogen Ralstonia solanacearum was firstly measured. The MC conversion of 98.83% ± 0.76% and CAPE yield of 96.29% ± 0.07% were obtained by response surface methodology in the 25 g/L TOPO-cyclohexane/[Bmim][Tf(2)N] (1:1, v/v); the complex stoichiometry calculation and FTIR spectrum confirmed that the reversible hydrogen-bond complexation between TOPO and caffeates significantly enhances the cooperative effect of two phases on the lipase-catalyzed reaction. The temperature was reduced by 14 °C; the MC concentration increased by 3.33-fold; the ratio of catalyst to donor decreased by 4.5-fold; and Km decreased 1.08-fold. The EC(50) of CAPE against R. solanacearum was 0.17–0.75 mg/mL, suggesting that CAPE is a potential in vitro inhibitor of plant pathogenic bacteria.